Dimensions of Service Quality in Influencing Customer Satisfaction - Noor, Iqbal; Alhidayatullah, Alhidayatullah; Amal, Muhammad Khairul (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Physical evidence, reliability, responsiveness, assurance, and empathy are one of the service factors that can provide satisfaction to consumers. The phenomenon that occurs in CV Agung Dipo Persada is that the services provided to consumers have not been optimal. This study aims to determine the level of customer satisfaction through the dimensions of service quality of CV Agung Dipo Persada both partially and simultaneously. Data from this study are consumers of CV Agung Dipo Persada with a population of 1,500 people. The sampling technique in this study used a web raosof.com sample size with an error rate of 5% so a sample of 306 respondents was obtained. Distribution of questionnaires as a data collection strategy. Multiple linear regression is the analysis technique used. According to the findings, tangible proof, dependability, responsiveness, assurance, and empathy had a positive influence on consumer satisfaction to the extent of 79.4%, while other variables influenced another 20.6%. The dominant variable had an impact, namely physical evidence of 67.3%, while the variable that had no effect was the reliability variable. The contribution of this study is to expand marketing management literature related to the dimensions of service quality and customer satisfaction in the context of organizations.